(untitled) (Ocean and Coastal Research, 2024)
Mangrove forests play a critical role in natural disaster resistance and provide meaningful livelihoods for localcommunities, especially integrated mangrove shrimp farming (IMSF) systems. Organic shrimp certification actuallyincreases the value chains of shrimp farming in addition to ameliorating mangrove–forest management. Identifyingtechnical issues and assessing environmental risks are the leading concerns when considering organic shrimpproduction certification. In this study, the technical practices of 30 households were investigated, and surface waterand sediment samples were collected in the IMSF models and adjacent rivers in the Thua Duc Forest ManagementBoard area, Ben Tre Province. Data collected from shrimp farming ponds and the environmental backgroundwere referred to both the Naturland and National Standards. The results showed that the average mangroveforest and shrimp pond ratio was 56.90:42.70 (%). Two technical issues were highlighted: (i) the use of rotenone,known as a toxin to kill undesirable fish before stocking shrimp, and (ii) annual shrimp pond regeneration causingincreased pollution. The data showed that higher concentrations of TSS and P-PO43- were detected in surroundingrivers, while surface water in either IMSF ponds or adjacent rivers slightly surpassed the permissible levels oftotal Fe concentration. All parameters—including heavy metals; toxic and persistent parameters; oil and greaseand coliforms analysed in surface water, and sediment samples—were lower than the detection and permissiblelevels. The results provided evidence that the IMSF’s practices and environmental characteristics were suitable forrecommending the Naturland Standards. Recommendations and technical interventions for farmers are necessaryto help reduce Fe levels and the safe use of rotenone in IMSF systems. An environmental quality monitoringprogramme at the target area should be applied when launching organic shrimp production.